Primary pancreatic lymphoma: diagnostic pitfall of an uncommon medical entity mimicking operable pancreatic carcinoma: case report and review of literature - Manchikanti, Dinesh; Aggarwal, Manisha; Kundaikar, Janitta; Thomas, Shaji; Arsia, Ashish; Pusuluri, Rahul; Meena, Kusum; Kumar, Sanjay (International Surgery Journal, 2021)
Almost all pancreatic neoplasms, including the commonest pancreatic ductal adenocarcinoma (PDAC) are derived from pancreatic epithelial components. Primary pancreatic lymphoma (PPL) is rare, accounting for less than 0.5% of all primary pancreatic tumours and presents a diagnostic and therapeutic challenge owing to their rarity, difficult access, and clinical and imaging features, which can mimic PDAC. A 26-year-old man presented with pain abdomen, jaundice, anorexia and weight loss for two months, along with two episodes of hematemesis and melena. Examination revealed an icteric patient with no palpable abdominal lump. His had a serum bilirubin of 13.6 mg/dl. His ultrasound abdomen, CT scan and MRCP showed a mass in the head and uncinate process of the pancreas with circumferential nodular thickening in second part of duodenum. Side viewing endoscopy was suggestive of carcinoma head of pancreas with duodenal infiltration, for which endoscopic biopsy was taken which revealed non-Hodgkin's lymphoma B cell type. A PET CT showed a metabolically active mass lesion in the head of pancreas, with no other focus of disease anywhere else, suggestive of primary pancreatic lymphoma. This patient was referred to Medical oncology and started on chemotherapy. Lymphoma should be considered when a large, homogeneous, hypoenhancing mass is encountered in the pancreatic head, and with bulky lymphadenopathy. Preoperative tissue diagnosis such as fine needle aspiration cytology with or without flow cytometry and/or laparoscopy/endoscopy guided tissue biopsy may be necessary. It is crucial to differentiate PPL from pancreatic adenocarcinoma since their treatment is primarily medical and prognosis differs considerably.